The human immunodeficiency virus (HIV)-type 1 coreceptor CXCR-4 (fusin) is preferentially expressed on the more immature CD34+ hematopoietic stem cells - Viardot, Andreas; Kronenwett, Ralf; Deichmann, Martin; Haas, Rainer (Annals of hematology, 1998)
In synergy with the CD4 antigen, the chemokine receptor CXCR-4 functions as a coreceptor for T-cell-tropic HIV-1 strains. Using two- and three-color immunofluorescence analysis, we examined the expression of CXCR-4 on CD34+ cells in 21 samples obtained from leukapheresis (LP) products of cancer patients who underwent G-CSF-supported cytotoxic chemotherapy. In addition, eight samples from bone marrow (BM) were obtained. CXCR-4 was expressed on the surface of CD34+ cells from samples of both hematopoietic sources. The mean proportion of CD34+/CXCR-4+ cells from LP products was 1.7-fold greater in comparison with those from bone marrow (65.9±4.1% vs. 37.5±8.6% [±SEM], p<0.05). For an intraindividual comparison, LP products and bone marrow from six patients were obtained on the same day, confirming the significantly greater proportion of CD34 + cells coexpressing CXCR-4 cells in LP products. In order to examine whether the CXCR-4 expression was related to the stage of maturation and differentiation of CD34+ cells, six samples from LP products and four samples from bone marrow were assessed using three-color immunofluorescence analysis. We found that the subset of CD34+/CD38low and CD34+/HLA-DRlow cells representing a population of more immature progenitor cells were brightly positive for CXCR-4, while there was a decrease in the level of CXCR-4 expression in the population of CD34+/HLA-DRbright and CD34+/CD38bright cells. Based on the assessment of ten LP products, we found that the mean proportion of CD34+ cells coexpressing CD4 and CXCR-4 was 6.2±2.3% [±SEM], suggesting that a small population of CD34+ cells are, in principle, susceptible for an infection with T-cell-tropic HIV-1 strains. In conclusion, our data suggest that CXCR-4 is present on the surface of hematopoietic progenitor cells - particularly more primitive CD34+ cells. CXCR-4 could play a role in the homing of CD34+ cells to stromal elements of the bone marrow via its natural ligand stromal-derived factor-1 (SDF-1).
Gesehen am 13.05.2025